Genetic predictors of five-year outcomes of acute coronary syndrome - N. G. Lozhkina; A. A. Tolmacheva; M. X. Khasanova; V. A. Kozik; E. A. Stafeeva; E. A. Naydena; I. Mukaramov; V. B. Barbarich; O. M. Parkhomenko; A. D. Kuimov; V. N. Maksimov; M. I. Voevoda (Российский кардиологический журнал)
Aim. To determine the genetic predictors of five-year outcomes in patients with acute coronary syndrome (ACS).Material and methods. The study included patients admitted to the City clinical hospital № 1 (CCH №1) in Novosibirsk with a diagnosis of ACS in the period 2010-3 2011 (n=280). All patients were examined in accordance with clinical guidelines and standards of care, genetic markers were assessed. Genotyping included determination of single nucleotide polymorphisms (SNPs), confirming its association with the development of the ACS according to the results of an international genomeassociated studies: rs1376251, rs4804611, rs 1333049, rs619203, rs10757278, rs2549513, rs499818, rs17465637. All patients are kept in touch from the moment of initial contact to the present time, with the help of available means of communication and annual examinations in order to assess the end points. “End points” included: repeated nonfatal myocardial infarction (MI), hospitalization for myocardial ischemia, re-revascularization or chronic heart failure (CHF), nonfatal acute cerebrovascular accident (NACA), cardiovascular death.Results. We revealed SNPs, which play a role in predicting long-term outcomes of ACS: rs10757278, rs 4804611, rs 1333049, rs 2549513. The genotype of rs2549513 as 2,9-fold (95% CI 1,06-8,03; p=0,041) increases the risk of unfavorable long-term prognosis in the subgroup of men older than 55 years. The AA genotype rs10757278 and GG genotype rs1333049 are associated with a favorable long-term prognosis (OR=0,47, 95% CI 0,23-0,96; p=0,042 and OR=0,41, 95% CI 0,22-0,78; p=0,049, respectively) in the group of patients older than 55 years. For the GG genotype rs1333049 association was characteristic only for women. The AA genotype rs4804611 is associated with a favorable outcome of ACS at the age of 55 years (OR=0,036, 95% CI 0,14-0,96; p=0,053), significant differences were obtained in the group of men (p=0,36).Conclusion. The use of identified genetic predictors to assess the risk of five-year outcomes will strengthen a personalized approach to patients and, together with conventional prevention measures, will reduce cardiovascular mortality.